Alternative Conceptions of Astronomy in Students of Basic and High School in the Metropolitan Region of Chile - Vanegas-Ortega, C (Universidad Austral de Chile, 2021)
The learning of Astronomy has presented various difficulties that, in part, have their origin in the alternative conceptions of the students. This study sought to identify recurring alternative conceptions of Astronomy in eighth grade and fourth year of high school students in the Metropolitan Region of Chile. For this, a multiplechoice test and focus groups has been implemented, with which quantitative and qualitative aspects of alternative conceptions were identified. The results show that students in eighth grade present alternative concepts with more frequently than those in the fourth year of secondary education, however, in the topic of “Seasons of the year”, both groups present a similar recurrence, while, when addressing the “Movements of the Sun in the sky”, it was observed that the group of fourth year of high school, it presents the alternative conceptions with more recurrence than the group of eighth grade. © 2021. All Rights Reserved.